Stigmatization of drinking patients with liver cancer: The role of socioeconomic status - Camille Auriol; Patrick Raynal; Nicole Cantisano (Heliyon, 2024)
Patients with liver cancer may face stigmatization due to cancer, alcohol consumption, or both. This study addresses gaps in the existing literature regarding stigmatization of alcohol-related liver cancer patients, particularly its connection with socioeconomic status (SES). The study explores whether the SES of a fictional character with alcohol addiction and liver cancer influences stigma levels reported by participants. Additionally, it investigates how participants' personal characteristics, such as alcohol consumption and healthcare professional status, impact stigmatization. This study aims to provide new insights regarding the role of stigmatization in liver cancer treatment and management, emphasizing in socioeconomic determinants. The method is based on three scenarios describing a woman character with alcohol abuse and liver cancer. The scenarios depicted a woman character with either low, medium or high SES. Each participant (N = 991) was randomly assigned to one of the three scenarios. After reading it, each participant answered questionnaires assessing negative attitudes towards the character. Four scales were used: “Negative attributions about people with health problems”, “Causality of cancer”, “Controllability of drinking” and “Reluctance to helping behavior”. Data were analyzed using ANOVA and t-tests. The scenario describing a character with a low SES significantly received more “Negative attributions about people with health problems” than the character with medium or high SES. Participants having higher alcohol consumption themselves showed lower stigma scores for three out of four scales than participants with lower consumption. In addition, participants identified as health professionals had lower stigma scores regarding the scales “Negative attributions about people with health problems” and “Controllability of drinking”, and higher scores for the subscale “Reluctance to helping behavior”, compared with non-professionals. A character with low SES received more negative attributions than the one with higher SES. Participants’ own alcohol consumption and professional status (being health professional or not), influenced their stigmatizing attitudes.